Transesterificotion for biodiesel production using Thespesia populnea seed oil: an optimization study - Rashid, Umer; Anwar, Farooq; Yunus, Robiah; Al-Muhtaseb, Alaa H. (Taylor & Francis Inc., 2015)
Due to the rapidly growing demand of vegetable oils for edible purposes, the use of non-edible seed oils are gaining much appreciation for biodiesel production. Biodiesel quality and production is affected by several process parameters. The present work was carried out to optimize the operational variables such as methanol/oil molar ratio (3:1–9:1), catalyst concentration (0.50%–1.30%, in relation to oil mass), temperature (45°C to 70°C), and mixing intensity (350–800 rpm) at fixed reaction time (120 min). Biodiesel was synthesized by transesterification of Thespesia populnea seed oil with methanol, using sodium hydroxide, potassium hydroxide, sodium methoxide, and potassium methoxide as catalysts. The optimum set of transesterifications reaction conditions: 7:1 molar ratio of methanol/oil, 65°C temperature, 0.90% (oil weight basis) NaOCH3 catalyst, and 650 rpm yielded 98.1% Thespesia populnea oil methyl esters (TPOMEs)/biodiesel. In summary, it could be concluded that Thespesia populnea oil as a non-food feedstock can be transformed into biodiesel with high yield (98.1%) under an optimized set of transesterification conditions.